2012
DOI: 10.1002/cc.20015
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of Workforce Baccalaureate Degrees in Florida

Abstract: This chapter highlights the history of workforce baccalaureate degrees in Florida, documents the growth of these programs across the state, and provides a framework for the designation of various degree types and academic requirements. Florida's new College System is described as one of the largest and most innovative systems of higher education for increasing access to four‐year workforce baccalaureates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“…Earlier work has suggested that CCB degree programs are typically offered to address local workforce shortages in high-demand fields (Bilsky, Neuhard, & Locke, 2012; Daugherty, Goldman, Butterfield, & Miller, 2014; Floyd, Falconetti, & Hrabak, 2008; Hanson, 2009; Walker, 2005), such as teacher education, nursing, and information technology (Daun-Barnett & Escalante, 2014). Because CCB degree programs were concentrated within applied fields with local workforce shortages, CCB adoption was designed to complement nearby four-year institutions and allow many underserved students to gain access to the benefits associated with earning a bachelor’s degree (Bilsky et al, 2012; England-Siegerdt & Andreas, 2012; Floyd, 2006; McKinney & Morris, 2010; Padrón, 2004; Russell, 2010), particularly place-bound and lower-income students (Floyd & Walker, 2009).…”
Section: Policy Context: the Origin And Purpose Of Ccb Degree Programsmentioning
confidence: 99%
“…Earlier work has suggested that CCB degree programs are typically offered to address local workforce shortages in high-demand fields (Bilsky, Neuhard, & Locke, 2012; Daugherty, Goldman, Butterfield, & Miller, 2014; Floyd, Falconetti, & Hrabak, 2008; Hanson, 2009; Walker, 2005), such as teacher education, nursing, and information technology (Daun-Barnett & Escalante, 2014). Because CCB degree programs were concentrated within applied fields with local workforce shortages, CCB adoption was designed to complement nearby four-year institutions and allow many underserved students to gain access to the benefits associated with earning a bachelor’s degree (Bilsky et al, 2012; England-Siegerdt & Andreas, 2012; Floyd, 2006; McKinney & Morris, 2010; Padrón, 2004; Russell, 2010), particularly place-bound and lower-income students (Floyd & Walker, 2009).…”
Section: Policy Context: the Origin And Purpose Of Ccb Degree Programsmentioning
confidence: 99%
“…All states initially put restrictions on the number of institutions allowed to offer the CCB, and/or the fields of study partially to address concerns of universities (Bilsky, Neuhard, & Locke, 2012). For example Florida required community colleges to seek a release from universities that they were not interested in offering the same degree, and Washington first restricted degree granting authority to four institutions with one degree each.…”
Section: Justification For the Research Problemmentioning
confidence: 99%
“…These include a substantive change proposal to a regional accrediting body seeking an institution status change to baccalaureate degree granting, possibly program specific accreditation, and internal governance procedures to the institution or system for program and curriculum approval. Scholars have presented case studies of authorization in particular states (Remington & Remington, 2005) with Florida being the subject of several studies given its longevity and national attention (Campbell, 2005;Floyd, Garcia Falconetti, & Hrabak, 2008;Bilsky, Neuhard, & Locke, 2012, Campbell, 2014, Henderson, 2014. Washington is another leader among the 50 United States (England-Siegerdt, & Andreas, 2012).…”
Section: Diffusion Of the Ccbmentioning
confidence: 99%
See 2 more Smart Citations